Coupling Of Geographic Information System And Optimization Method With Congestion Consideration To Support Urban Freight Transport - Yudha Prambudia (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2008)
The study aimed to evaluate focus and quality of Indonesian e-government website. All 456 websites of districts/cities throughout the country are taken into account. The study revealed that 66.9% of districts/cities had their own website and were in operations, while other were either still embedded into website of province, not found, or inaccessible. In general, the websites focused on promoting linkage between government and business, while efficiency and effectiveness in the delivery of frontline services were less prioritized. The quality of the website in general was in medium level, both in terms of the quality of content and the level of ease-of-use. Keywords: e-government website, website focus, website quality, Indonesia.